Mobile Banking and Financial Inclusion : The Regulatory Lessons - Klein, Michael (2012)
Mobile banking is growing at a remarkable speed around the world. In the process it is creating considerable uncertainty about the appropriate regulatory response to this newly emerging service. This paper sets out a framework for considering the design of regulation of mobile banking. Since it lies at the interface between financial services and telecoms, mobile banking also raises competition policy and interoperability issues that are discussed in the paper. Finally, by unbundling payments services into its component parts, mobile banking provides important lessons for the design of financial regulation more generally in developed as well as developing economies.